Primary health care and equity: the case of lesbian, gay, bisexual, trans and intersex Australians - Rosenstreich, G.; Comfort, Jude; Martin, P. (CSIRO, 2011)
The current period of health reform in Australia offers an opportunity for positive actions to be taken to address the significant challenges that lesbian, gay, bisexual, trans, intersex and other sexuality, sex and gender diverse (LGBTI) people face in the health system. This paper provides analysis of why this group should be considered a priority health group using a social determinants of health framework, which has, to date, largely been ignored within primary health care policy reform in Australia. Several key areas of the primary health care reform package are considered in relation to LGBTI health and well-being. Practical suggestions are provided as to how the primary health care sector could contribute to reducing the health inequities affecting LGBTI people. It is argued that care needs to be taken to ensure the reform process does not further marginalise this group.